Influência do jateamento do vidro bioativo 45S5 na dentina hipomineralizada para longevidade de restaurações semi-diretas: estudo in vitro e ensaio clínico randomizado boca dividida - SILVA, Dyele Kalynne Costa da (2025)
Molar Incisor Hypomineralization (MIH) is a qualitative defect in the enamel, structurally characterized by a significant reduction in calcium (Ca) and phosphorus (P) and an increase in carbon (C), the adhesion is difficult in this tissue and no have alternatives of treatment in severe cases. Bioactive materials have been widely studied due to remineralizing potential, increasing the amount of calcium and phosphate ions, which can reduce dentin sensitivity and adhesion to dentin. The aim of chapter I was an in vitro study to evaluate the influence of air abrasion with Bioglass 45S5 (Bioactive Glass-BAG) on microhardness and bond strength (BS) in dentin with induced hypomineralization (IH). Materials and Methods: Dentin blocks were randomized and treated (n= 60): sound dentin (D), BAG-air abrasion in sound dentin (D-BAG), IH dentin (HD) and BAG-air abrasion in IH dentin (HD-BAG). Knoop hardness (KH) and SEM/EDS of dentin were initially verified in sound dentin (T0) (D, HD, D-BAG and HD_BAG), after induction of hypomineralization (T1) (HD e HD-BAG), after air abrasion with BAG (T2) (D-BAG and HD-BAG) and after shearing (T3) (D, HD, D-BAG and HD_BAG). The air abrasion protocol consisted of three air abrasion sessions (once for week) for 1 minute at 90o with BAG. For the shear test, blocks of nanoparticle composite resin were made and fixed in the experimental groups with Set PP cement (SDI). The samples were stored for 1 week at 37oC and subjected to the shear test. The failure mode and dentin surface were evaluated by stereomicroscope, SEM and EDS. Data were statistically analyzed by one- way ANOVA and post-hoc Tukey (p<0.05). For KH, there was a decrease in values at times T0-T1 (D and HD) and an increase in T1-T2 (HD and HD-BAG) (p<0.05). The highest BS values were found for D and D-BAG, and the lowest values in HD, however, HD-BAG showed no difference between the groups studied. SEM and EDS analysis demonstrated calcium and phosphorus precipitates in the air abrasion groups (BAG). It is concluded that air abrasion with BAG increases the KH of IH dentin and promotes BS similar to sound dentin. The aim of chapter II was a split-mouth randomized clinical trial was to verify the influence of the air abrasion with 45S5 bioglass (BAG) in teeth with MIH prior to cementation of semi-direct restorations (SDR). Methodology: Patients between 9 and 20 years of age were selected, totaling 28 first permanent molars with Nolla stage 8-10 and severe MIH lesions. After clinical evaluation, molars with painful hypersensitivity and at least 2 surfaces affected by MIH, with yellow-brown coloration, were found. Onlay preparations were planned and these teeth were prepared, randomized and divided in 2 groups according to the treatments: MIH - untreated dentin, and MIH- BAG - dentin previously treated with air abrasion with BAG. The teeth of the MIH-BAG group were treated with air abrasion with BAG 3 times and protected with provisional restoration. The RSD were made using the flexible matrix technique, using Z350XT(3M) nanoparticle composite resin and cemented with bioactive and self-adhesive cement (SetPP, SDI), on the prepared teeth. The treated teeth were evaluated after 1 and 6 months of treatment, Using Fisher's exact test, and absolute and relative frequencies (%) of the scores to analyze retention and functional variables (FDI criteria) (p > 0.05). Results: No significant difference was observed between the frequencies of the treatment types (MIH and MIH-BAG), regardless of the evaluation time (p>0.05) and the esthetic, functional and biological variables were affected by the type of treatment (p>0.05). Conclusion: Air abrasion with 45S5 in young permanent molars with MIH previously to SDR cementation allowed retention of the restorations and absence of sensitivity, with satisfactory esthetic, functional and biological results over the 6 months of follow-up.